MANAJEMEN PENDIDIKAN BIMBINGAN DAN KONSELING DI SMA 19 MUARA BUNGO, DESA BUKIT SARI, KECAMATAN JUJUHAN ILIR - Lesis Andre; Neviyarni Neviyarni; Riska Ahmad; Yarmis Syukur (Center for Research and Community Service (LPPM) University of Abulyatama, 2022)
: This article is intended to the implementation of the management of Counseling Guidance Education at SMAN 19 Muaro Bungo, Bukit Sari Village, Jujuhan Ilir Subdistrict. The method used is qualitative with phenomenological approach. SMAN 19 Muaro Bungo was used as a research object. The data source was obtained from the principal, BK teacher, and SMAN 19 student Muaro Bungo. Data collection using interviews, observations, and documentation. The implementation of Education Guidance and Counseling management is carried out through four steps, namely planning, implementation, supervision, and evaluation. Kempat Step on education management guidance and counseling at SMAN 19 Muaro Bungo has been done well. There is one step that needs to be applied to strengthen the management of guidance and counseling education at SMAN 19 Muaro Bungo, namely conducting consultation stages from parents, BK teachers, and principals. If this application is less able to find a solution, then an inverted pattern is applied, namely from the principal, bk teachers, and parents.